2016
DOI: 10.3389/fpls.2016.01144
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Photosynthetic, and Physiological Responses of Rapeseed Leaf to Different Combinations of Red and Blue Lights at the Rosette Stage

Abstract: Rapeseed (Brassica napus L.) is sensitive to light quality. The factory production of rapeseed seedlings for vegetable use and for transplanting in the field requires an investigation of the responses of rapeseed to light quality. This study evaluated the responses of the leaf of rapeseed (cv. “Zhongshuang 11”) to different ratios of red-photonflux (RPF) and blue-photonflux (BPF) from light emitting diodes (LEDs). The treatments were set as monochromatic lights, including 100R:0B% and 0R:100B%, and compound li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
54
3
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 52 publications
(77 reference statements)
14
54
3
3
Order By: Relevance
“…Plants grown under 0B, 50B and 100B conditions had similar lower values of shoot, root FW and DW (Figure 3). Our results of ice plants agree with the finding from many other studies that supplementing optimal amount of blue light to red light is necessary to achieve greater biomass accumulation [18,21,29,39,61,62] . However, similar to the 0B condition the stronger blue-LEDs such as 50B and 100B resulted in reduction of biomass accumulation in ice plant (Figure 3).…”
Section: High B:r-led Ratios Lead To the Decline In Productivity But supporting
confidence: 92%
See 2 more Smart Citations
“…Plants grown under 0B, 50B and 100B conditions had similar lower values of shoot, root FW and DW (Figure 3). Our results of ice plants agree with the finding from many other studies that supplementing optimal amount of blue light to red light is necessary to achieve greater biomass accumulation [18,21,29,39,61,62] . However, similar to the 0B condition the stronger blue-LEDs such as 50B and 100B resulted in reduction of biomass accumulation in ice plant (Figure 3).…”
Section: High B:r-led Ratios Lead To the Decline In Productivity But supporting
confidence: 92%
“…Compared to R-LED alone (0B), all combined RB-LEDs promote leaf growth and development, dry matter accumulation and photosynthesis of Chinese broccoli ( Figure 1 and Table 1). These results support the notion that for certain species any level of blue light regulates leaf development and photosynthetic performance [18,36] . In other words, blue light alleviate "red light syndrome" such as a low photosynthetic rate, low LMA, unresponsive stomatal conductance and impaired shoot and root growth [7,36,39,51] .…”
Section: Productivity Is Closely Linked To Both the Photosynthetic Pesupporting
confidence: 87%
See 1 more Smart Citation
“…Yield of lettuce, spinach, and radish crops grown under appropriate combination of red and blue light was enhanced compared to red light alone (Yorio et al, 2001). Similar results were found in strawberry plantlet (Nhut et al, 2003), rapeseed ( Brassica napus L.) plantlets in vitro (Li et al, 2013), rapeseed rosette leaves (Shengxin et al, 2016), and cucumber seedlings (Hernández and Kubota, 2016; Trouwborst et al, 2016). In a recent developed highly energy-efficient laser-illuminated growth chamber, Ooi et al (2016) also showed that the application of diffused single-wavelength red and blue laser light is adequate for the growth and development of Arabidopsis thaliana .…”
Section: Introductionsupporting
confidence: 78%
“…It was observed that lettuce and other dicotyledonous plants developed excessive hypocotyl and stem elongation, leaf extension, and reduced chlorophyll (Chl) when grown under red-LED as the sole source of irradiation. The abnormal morphological characteristics were eliminated when red-LED was supplemented with blue light (Bula et al, 1991; Yorio et al, 2001; Nhut et al, 2003; Li et al, 2013; Hernández and Kubota, 2016; Shengxin et al, 2016; Wang et al, 2016). Yield of lettuce, spinach, and radish crops grown under appropriate combination of red and blue light was enhanced compared to red light alone (Yorio et al, 2001).…”
Section: Introductionmentioning
confidence: 99%